2019
DOI: 10.3389/fphys.2019.00239
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Contractile Function of Permeabilized Human Hypertrophic Cardiomyopathy Multicellular Heart Tissue

Abstract: Background : Many forms of hypertrophic cardiomyopathy (HCM) show an increased myofilament Ca 2+ sensitivity. This observation has been mainly made in HCM mouse models, myofilament systems, and cardiomyocytes. Studies of multicellular tissues from patients with different HCM-associated gene mutations are scarce. We investigated Ca 2+ sensitivity in multicellular cardiac muscle strips of HCM patients. We furthermore evaluated the use of epigallocatechin-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
1
8
0
Order By: Relevance
“…6 D). This suggests that this MYBPC3 mutation may prolong APD and therefore contribute to arrhythmias in the HCM patient, which could be related to the previously measured higher myofilament Ca 2+ sensitivity [ 47 ]. For the other HCM samples, however, the APD did not significantly differ to samples from patients with aortic stenosis.…”
Section: Discussionmentioning
confidence: 90%
“…6 D). This suggests that this MYBPC3 mutation may prolong APD and therefore contribute to arrhythmias in the HCM patient, which could be related to the previously measured higher myofilament Ca 2+ sensitivity [ 47 ]. For the other HCM samples, however, the APD did not significantly differ to samples from patients with aortic stenosis.…”
Section: Discussionmentioning
confidence: 90%
“…We further selected an example of one down-regulated and one up-regulated gene and examined them in more detail to demonstrate the strength of our integrative omic analysis. ATP2A2 , one protein-coding gene from the overlapping candidates, encodes the sarcoplasmic reticulum Ca2+ -ATPase pump SERCA2a and plays a critical role in the regulation of calcium handling [ 14 ]. We identified ATP2A2 as one of the major candidates in discriminating HCM hearts from controls in our integrated H3K27ac ChIP-seq and RNA-seq analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among these, ATP2A2 /SERCA2a, the cardiomyocyte-specific marker, transports cytosolic calcium into the sarcoplasmic reticulum and subsequently regulates the contraction and relaxation of cardiomyocytes [ 18 ]. Suppressed ATP2A2 /SERCA2a expression is associated with impaired relaxation in cardiomyocytes and contributes to diastolic dysfunction in HCM [ 14 , 19 ]. Consistent with previous findings, we also showed lower mRNA and protein levels in HCM hearts compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…The prevention of the EHT disease phenotype after Mybpc3 D282 and S282 gene transfer was expected in both conditions since the amount of cMyBP-C protein was completely restored, and we recently showed that ≥73% of wild-type cMyBP-C in a Mybpc3 null background is enough to overcome the disease phenotype 17 . Increased myofilament [Ca 2+ ] sensitivity is a well-accepted hallmark of HCM as seen in human samples 11,36,47,48 and in HCM animal models 15,17,35,4953 . Accordingly, KI-NT showed higher sensitivity to external [Ca 2+ ] than WT EHTs.…”
Section: Discussionmentioning
confidence: 99%
“…Force-calcium relationship data were analyzed using the Hill equation, with EC 50 as the free Ca 2+ concentration, which yields 50% of the maximal force and nH representing the Hill coefficient. Curves were fitted to the data points and force-pCa relationship comparison was done by using extra sum-of-squares F-test 48 . A value of P < 0.05 was considered statistically significant.…”
Section: Methodsmentioning
confidence: 99%